PEMBERIAN RESTITUSI TERHADAP ANAK SEBAGAI KORBAN KEKERASAN SEKSUAL - Vedy Riza Alhabsy (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The existence of children's rights as victims of sexual violence has not been fully fulfilled, because in reality restitution is often not carried out properly. This is caused by several factors, such as the lack of awareness of the perpetrators of their responsibilities, the difficulty in obtaining sufficient evidence or information, and the lack of supervision and law enforcement regarding the implementation of restitution. This study aims whether child victims of sexual violence have the right to receive restitution, and how are efforts to provide restitution for children as victims of sexual violence cases. This study uses normative legal research with a statutory approach. The results of this study are first, child victims of sexual violence have the right to receive restitution in Article 71D of Law number 35 of 2014 concerning amendments to Law number 23 of 2002 concerning Child Protection, jo article 7A in Law number 31 of 2014 concerning amendments to Law number 13 of 2006 concerning Protection of Witnesses and Victims. Second, what are the efforts to provide restitution for children as victims of sexual violence cases Article 7A paragraph (1) Law Number 31 of 2014 concerning the Protection of Witnesses and Victims that every victim has the right to obtain restitution, Government Regulation Number 43 of 2017 regarding the implementation of restitution for children who are victims, namely regarding the Rights of Child Victims in prosecution.